An unfinished song - Svarṇakumārī Debī.; Vijayasree, C. (New Delhi : Oxford University Press, 2008)
Translation of a Bengali novel.
Includes bibliographical references (p. 94-100).
Keywords: Bengali fiction -- Translations into English